Prevalence of dysglycaemia in rural Andhra Pradesh: 2005, 2010, and 2014: 2005、2010以及2014年安得拉邦农村的糖代谢异常患病率. (28th January 2016) - Affan, Eshan T.; Praveen, Devarsetty; Wu, Jason H.Y.; Chow, Clara K.; Peiris, David; Patel, Anushka; Neal, Bruce C.
Abstract: Background: Communities in rural Andhra Pradesh may be at increasing risk of diabetes. In the present study we analyzed three cross‐sectional studies over 9 years to estimate the changing prevalence of dysglycemia (diabetes and prediabetes). Methods: The 2005 study sampled 4535 individuals from 20 villages, the 2010 study sampled 4024 individuals from 14 villages, and the 2014 project of 62 254 individuals sought to include all adults aged 40–85 years from 54 villages. Blood glucose levels were estimated using a hand‐held device in 2005 and 2014 and using HbA1c dried blood spots in 2010. Results: In primary analyses restricted to assays based on fasting samples (2005, n = 3243; 2014, n = 749), the prevalence estimates for dysglycemia were 53.7% (95% confidence interval [CI] 51.8%–55.7%) in 2005 and 62.0% (95% CI 58.5%–65.4%) in 2014 ( P < 0.001). Over the same period, mean body mass index (BMI) increased from 22.2 to 24.3 kg/m 2 (mean difference 2.1 kg/m 2 ; 95% CI 2.0–2.2 kg/m 2 ; P < 0.001). In secondary analyses using data from all participants (2005, n = 4535; 2010, n = 4024; 2014, n = 62 254), regardless of measurement technique, the estimated prevalence of dysglycemia was 53.9% (95% CI 52.0%–55.9%) in 2005, 50.5% (95% CI 46.1%–54.9%) in 2010, and 41.3% (95% CI 40.9%–41.7%) in 2014 ( P < 0.001). Conclusions: The prevalence of dysglycemia was high at every assessment using every measurement method. Dysglycemia in this population is most likely to have risen with the rise in BMI. The decline in prevalence suggested by the secondary analyses was likely due to confounding from the different assessment methods. Abstract : Prevalence of diabetes and prediabetes in 2005, 2010, and 2014 in all adults regardless of assessment method (secondary analyses).